2020
DOI: 10.1108/pijpsm-06-2019-0094
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting emotional labor and burnout in civilian and sworn law enforcement personnel

Abstract: PurposeThis study introduces emotional labor into an analysis of multiple dimensions of burnout in sworn and civilian employees across three law enforcement agencies.Design/methodology/approachUsing data from a survey of law enforcement employees in a metropolitan police department, a full-service sheriff's department, and a state corrections agency located in the western United States (n = 1,921), we test the explanatory power of an emotional labor-based model of burnout.FindingsResults partially confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…We also found that there is a considerable risk of work-family conflict and work-life spillover (Westaby et al, 2016) and that probation staff have to perform a high level of surface acting as part of their job (Westaby et al, 2019). Surface acting -a concept taken from the literature on emotional labour (Hochschild, 1983) -has been linked to higher levels of burnout amongst workers in other criminal justice institutions (such as the prison (Nylander et al, 2011) and the police (Adams and Mastracci, 2020;Black and Lumsden, 2020;Schaible and Six, 2016) and other jurisdictions (e.g. the US).…”
Section: Introductionmentioning
confidence: 67%
“…We also found that there is a considerable risk of work-family conflict and work-life spillover (Westaby et al, 2016) and that probation staff have to perform a high level of surface acting as part of their job (Westaby et al, 2019). Surface acting -a concept taken from the literature on emotional labour (Hochschild, 1983) -has been linked to higher levels of burnout amongst workers in other criminal justice institutions (such as the prison (Nylander et al, 2011) and the police (Adams and Mastracci, 2020;Black and Lumsden, 2020;Schaible and Six, 2016) and other jurisdictions (e.g. the US).…”
Section: Introductionmentioning
confidence: 67%
“…This situation forced SLBs to make new or different decisions in their jobs every day. The interaction and emotional engagement of SLBs and police officers with citizens, along with work environments with a high workload, unpredictability and ambiguity, may lead to symptoms of distress (Braquehais et al, 2020;Riedy et al, 2021;Tummers et al, 2015); PTSD, anxiety, insomnia and/or depression (Navin et al, 2020;Pappa et al, 2020;Wagner et al, 2019); alienation, depersonalization, emotional exhaustion, surface acting, burnout (Adams and Mastracci, 2020), decoupling and coping practices (Johnson and Vaughn, 2016;Knight, 2017); or even increased risk of suicide mortality (Baumert et al, 2014).…”
Section: Responsementioning
confidence: 99%
“…, 2020; Wagner et al. , 2019); alienation, depersonalization, emotional exhaustion, surface acting, burnout (Adams and Mastracci, 2020), decoupling and coping practices (Johnson and Vaughn, 2016; Knight, 2017); or even increased risk of suicide mortality (Baumert et al. , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the deliverer, in the face of customers, merchants, platforms and other third-party personnel, the inconsistency between the false emotional expression and the inner reality brought by wearing the mask will consume more psychological resources and aggravate the psychological fatigue [8]. By actively adjusting their own subjective experience and inner expression, and providing services from the heart, to achieve an active deep performance that is consistent with the outside, the takeaway deliverers can improve their personal sense of accomplishment and job satisfaction [9]. Delivery personnel should strengthen their own active emotional labor strategy, and perform more deep roles in the process of delivery, so as to meet the requirements under various rules.…”
Section: Optimization Of Emotional Labor Management At the Employee Lmentioning
confidence: 99%